The manager strategy on developing human resources of nursing in the hospital - Harwanto, Tri; Arso, Septo Pawelas; Sulisno, Madya (Universitas Aisyah Pringsewu, 2020)
Hospital management must have a strategy to increase nursing resources to provide quality, effective and efficient nursing services. The purpose of this study is to determine the manager's strategy in developing human resources of nursing to improve professional competency education. This type of research used in this research is qualitative research. The subject and object of this research include the place, namely the situation and condition of the hospital environment, the nurses as the perpetrator and the parties around them, including the leader and the head of the room, the activity that is the development of nurse resources that has been carried out. This research was conducted at Limpung Regional Hospital of Batang Regency in August 2019 - November 2019. This research instrument uses in-depth interviews using interview guidelines and documentation to collect profiles of Limpung Regional Hospital, Batang Regency, and information data from various media sources related to the focus research. The data analysis used in this research is the Colaizzi model. This study's research results obtained 3 themes: strategies to improve nursing education, strategies to improve nurse competence and strategy to enhance professionalism and maintain nurse performance. The managers' strategy in developing human resources is needed to improve health services, especially nursing services. Abstrak: Manajemen rumah sakit harus memiliki strategi dalam upaya peningkatan sumber daya keperawatan sehingga mampu memberikan pelayanan keperawatan yang berkualitas, efektif dan efisien. Tujuan dalam penelitian ini adalah mengetahui strategi manager dalam mengembangkan SDM keperawatan untuk meningkatkan pendidikan kompetensi professional. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kualitatif. Subjek dan objek penelitian ini meliputi tempat yaitu situasi dan kondisi lingkungan Rumah Sakit, pelaku yaitu perawat dan para pihak yang ada di sekitarnya yang meliputi pimpinan dan kepala ruang, kegiatan yaitu kegiatan pengembangan sumber daya perawat yang telah dilakukan. Penelitian ini dilakukan di RSUD Limpung Kabupaten pada Bulan Agustus 2019 – November 2019.Instrumen penelitan ini menggunakan wawancara mendalam dengan menggunakan pedoman wawancara dan dokumentasi yang digunakan untuk mengumpulkan profil RSUD Limpung Kabupaten Batang, dan data-data informasi dari berbagai sumber media yang terkait dengan fokus penelitian. Analisa data yang digunakan dalam penelitian ini adalah model Colaizzi. Hasil penelitian dalam penelitian ini diperoleh 3 tema yaitu strategi untuk meningkatkan pendidikan keperawatan, strategi untuk meningkatkan kompetensi perawat dan strategi untuk meningkatkan professional dan mempertahankan kinerja perawat. Strategi manager dalam mengembangkan SDM Keperawatan sangat diperlukan untuk meningkatkan pelayanan kesehatan khsususnya pelayanan keperawatan.